Modeling of readout circuit for acquisition of sensory signal through non-contact means - Khan, Sheroz; Khan, Imran Moez; Bahri, Nur Aini Rahimah; M Saad@Md Saad, Nurul Wahida (2012)
This work is about modeling a readout system across narrow gaps using inductive means for a contact-less transfer of signal. The signal source could be devices implanted in humans or animals or even devices embedded buried in inaccessible locations for monitoring purposes, while the readout devices are normally in accessible locations in the external world. This work focuses on modeling the coupled coils used in the inductive coupling technique. The input impedance of the simplified model of the coupled coils as seen from the external readout circuit is derived. This impedance is plotted as a function of frequency for finding the points, at which the two coils get resonated, allowing signal transfer with a maximum strength. The preliminary simulations and derivation plots show that the impedance is dependent on the coupling coefficient of the coils. Larger is the value of coupling (that is smaller gap), better will be transmission of the signal. Assuming a load of small resistive value coupled with a capacitive element, the results of the effect of varying resistance for a fixed value of capacitance and the effect of a variable capacitance for a fixed value of resistance are obtained. Such results are supported by PSpice simulation, showing consistency of the basic concepts used.